ZmDREB2.9 Gene in Maize (Zea mays L.): Genome-Wide Identification, Characterization, Expression, and Stress Response - Mikhail A. Filyushin; Elena Z. Kochieva; Anna V. Shchennikova (Plants, 2022)
Dehydration-responsive element-binding (DREB) transcription factors of the A2 subfamily play key roles in plant stress responses. In this study, we identified and characterized a new A2-type DREB gene, ZmDREB2.9, in the Zea mays cv. B73 genome and compared its expression profile with those of the known A2-type maize genes ZmDREB2.1–2.8. ZmDREB2.9 was mapped to chromosome 8, contained 18 predicted hormone- and stress-responsive cis-elements in the promoter, and had two splice isoforms: short ZmDREB2.9-S preferentially expressed in the leaves, embryos, and endosperm and long ZmDREB2.9-L expressed mostly in the male flowers, stamens, and ovaries. Phylogenetically, ZmDREB2.9 was closer to A. thaliana DREB2A than the other ZmDREB2 factors. ZmDREB2.9-S, ZmDREB2.2, and ZmDREB2.1/2A were upregulated in response to cold, drought, and abscisic acid and may play redundant roles in maize stress resistance. ZmDREB2.3, ZmDREB2.4, and ZmDREB2.6 were not expressed in seedlings and could be pseudogenes. ZmDREB2.7 and ZmDREB2.8 showed similar transcript accumulation in response to cold and abscisic acid and could be functionally redundant. Our results provide new data on Z. mays DREB2 factors, which can be used for further functional studies as well as in breeding programs to improve maize stress tolerance.